AN ANALYSIS OF SPEECH ACT USED IN THE WRITTEN CONVERSATIONS FROM ENGLISH TEXTBOOK FOR JUNIOR HIGH SCHOOL GRADE IX PUBLISHED BY THE MINISTRY OF EDUCATION AND CULTURE IN 2018 - Nadia Sari Refualu; Maria Arina Luardini; Maida Norahmi (Academic Journal of Educational Sciences, 2021)
The application of pragmatics often used in an English textbook, namely, Speech Act, is applied to state the action or intention of doing something indirectly so that the teachers, who are teaching the most students that did not really understand the various meanings from some conversations, should comprehend the context first by checking the type of speech act. The purposes of this research were to identify the types of speech acts found in the utterances of each conversation and to reveal the function of each speech act found in each utterance of every conversation contained in Bahasa Inggris (English): Think Globally Act Locally for Grade IX.The researcher employed the descriptive qualitative research. The most needed instrument was the researcher, and the secondary instrument was in the form of the data sheet. The primary source of the data was the textbook itself, and some downloaded books and journals are used to complete the data needed. For the data collection process, the researcher applied “observation”. The researcher also used the model of data analysis procedure named content analysis. For checking the trustworthiness of data, the researcher involved the four components called credibility, transferability, dependability, and confirmability. Based on the analysis conducted by the researcher, there were five types of speech act according to the Searle’s classification found in the textbook: assertive or representatives with 96 data (41.4%), both directives and expressive had the same number with 65 data (28.0%), commissives with 5 data (2.2%), and declarations with 1 datum (0.4%). For the second result, the researcher found that these five types of speech act with their own functions were all existed in two hundred and thirty-two utterances used by the speaker of each conversation in the textbook.